Bilgisayar destekli takı kalıbı tasarımı ve imalatı - Şen, Serkan (My University, 2005)
İstihdamı, üretimi, hem de ihracatı bir arada artıracak yatırım alanları arasında henüz denenmemiş ve bu amaçlara hizmet edebilecek sektörler incelendiğinde, kuyumculuk tüm bu amaçlara uygun bir sektör olarak karşımıza çıkmaktadır. Üretilen modellerin kullanıma sunulduğu bu pazarda, tüketicilerin altından ve diğer kuyumculuk metallerinden yapılmış takıların artık bir yatırım aracı olarak kullanılmasından ziyade, genel anlamda estetiği tamamlayıcı bir ürün olarak görmeye başlamalarıyla birlikte, talep arzı oluşturmuş ve takı imalatçıları tasarım çalışmalarına daha da önem vermeye başlamışlardır. Bu talebin artmasıyla birlikte imalatçılar pazarda söz sahibi olabilmeleri noktasında, kaliteli ve aynı zamanda hızlı tasarım ve imalat çalışmalarına yönelmek durumunda kalmışlardır. Dolayısıyla yeni bir ürünün tasarımında ve imalatında hız, üreticiler için çok önemli bir özelliği teşkil etmektedir. Bunun sonucu olarak ta kalıp tasarımları Bilgisayar Destekli olarak yapılmaya başlanmıştır. Bu çalışmada, takı malzemeleri, takı tasarım ve imalat yöntemleri modern teknolojiler ve literatürdeki bilgiler yardımıyla incelenmiştir. Takı tasarımında kullanılan JewelCAD programıyla yüzük tasarımı yapılmış ve imalatın gerçekleştirilmeye kadar yapılan aşamalar sistemli bir şekilde incelenerek, tasarım ve kalıp imalatı aşamalarında dikkat edilmesi gereken hususlar hakkında uygulamacıların ve bu konuda eğitim-öğretim yapan meslek okullarının yararlanabileceği bir çalışma hazırlanmıştır. The design of jewellery is a synthesis of artistic creativity and production technology. Over the ages, artisans, with their overwhelming imagination and creativity, have been looking for new materials and techniques and have been supported in their work by new materials and technologies. The need for improved weapons is said to have driven production technology, but the decoration of arms followed on immediately. These newly learned and adopted techniques then influenced the work of the designers in all other decorative areas and created fashions. The combination of precious materials, innovative production technology and excellent handicraft led to jewellery which is so specific for a particular period of time that the date of origin of relics can be determined. Today, the variety of available technologies is much broader and the speed of development is much faster and even accelerating. Also, fashions change faster and faster. The time frame to renew a jewellery collection gets shorter and severe competition forces manufacturers to present updated jewellery items. Also, the number of producers and the design competition in a global market continues to increase. Short innovation and production times become a leading edge in competitiveness. The aim of this thesis is to present a methodology for the design of jewellery mould systems and manufacturing jewellery technologies. The first part of the presentation studies of about jewellery academics or some manuals. The second part of the thesis are explained some mechanical properties of materials which used to made jewelery( gold, platin etc.). The third part of thesis was concerned with jewellery manufacture and design. The fourth part is explained stages of design and manufacturing a ring which is written Marmara University and logos on it. Finally, the fifth part of thesis is defined results of studies.
Keywords: Takı Tasarımı, Bilgisayarda